Il radicamento naturale delle arti: John Dewey nel dibattito contemporaneo - Roberta Dreon (Aisthesis, 2012)
This article discusses the question of the natural roots of arts in Dewey's thought. Starting from his general conception of human experience as interaction between an organism and its natural and social environment, such an interaction appears as qualitatively or aesthetically charged. In this perspective perception can not be confined to an only sensory sort of sensitiveness and much less be understood in the sense of the so called aesthetic differentiation. In the light of actual debate on naturalism Dewey's continuistic position appears naturalistic but not reductionistic and at the same time at least partially able to withstand some charges of mantaining foudationalist residues